A Comparative Study of CoNi-LDH/ZnO Film for Photocathodic Protection Applications in the Marine Environment - Zhang, Xuan; Wang, Yanhua; Zhang, Dongmei; Tao, Zhencheng (Frontiers in Materials, 2022)
In this paper, two kinds of CoNi-layer double hydroxide (LDH)/ZnO films were prepared with different morphologies by simple electrochemical method. The properties of the films were investigated by SEM, XRD, UV-vis DRS, XPS and the electrochemical techniques. It was found that the CoNi-LDH modified ZnO films exhibited excellent photocathodic properties in a scavenger-free environment. This is mainly due to the absorption of visible light by LDH, the formation of p-n heterojunction and the depletion of photogenerated holes by the cycling process of Co (Ⅱ)/Co (Ⅲ). Compared with CoNi-LDH/ZnO nanorods, CoNi-LDH/ZnO nanoclusters showed better photocathodic protection performance and physical barrier effect. Under illumination conditions, the rough surface of ZnO nanoclusters and the deposition of large amount of LDH can provide more photoelectrochemical active sites, thus improving the light absorption capacity and photocathodic protection performance of CoNi-LDH/ZnO nanoclusters. Under dark conditions, the physical barrier effect of CoNi-LDH/ZnO nanoclusters was also enhanced by the dense ZnO nanoclusters and thick CoNi-LDH layers.